SPECIAL AUTONOMY FUNDS AND REGIONAL ECONOMIC GROWTH : AN EMPIRICAL STUDY IN ACEH - El Shinta (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2025)
This study investigates the impact of Special Autonomy Funds (SAF) on regional economic growth in Aceh, Indonesia, a post-conflict province granted fiscal autonomy through Law No. 21/2001 and the 2005 Helsinki Agreement. Using a mixed-methods design, the research combines quantitative analysis of Gross Regional Product (GRP), employment, and poverty indicators from 2008–2022 with qualitative insights from 300 respondents, including government officials and community leaders. Regression results reveal that a 1% increase in SAF allocation corresponds to a 0.5% rise in GRP, underscoring SAF’s multiplier effect. The findings further demonstrate that SAF-supported investments in infrastructure, education, and healthcare contributed to poverty reduction from 20.5% in 2010 to 15.4% in 2021, and reduced unemployment from 5.5% to 4.2%. Qualitative evidence highlights the role of governance, community participation, and accountability mechanisms in enhancing fund effectiveness, though challenges such as corruption and bureaucratic inefficiency persist. The study contributes to fiscal decentralization literature by providing empirical evidence on autonomy funds in a post-conflict setting and offers policy recommendations to strengthen transparency, align SAF with long-term development priorities, and foster sustainable regional growth. These insights are relevant not only for Aceh but also for other regions with similar autonomy frameworks.